Epidemiology of extrapulmonary tuberculosis among pediatric inpatients in mainland China: a descriptive, multicenter study. Issue 1 (31st December 2022) - Chu, Ping; Chang, Yan; Zhang, Xuan; Han, Shujing; Jin, Yaqiong; Yu, Yongbo; Yang, Yeran; Feng, Guoshuang; Wang, Xinyu; Shen, Ying; Ni, Xin; Guo, Yongli; et al.
ABSTRACT : Pediatric tuberculosis (TB) is a serious infectious disease that affects many children worldwide and is more likely to be extrapulmonary than adult TB. However, the clinical and epidemiological profile, and cost burden of pediatric extrapulmonary TB (EPTB) in China remain unknown. Here, we conducted a descriptive, multicenter study of pediatric TB patients from 22 hospitals across all six regions in China from October 2015 to December 2018. Of 4, 654 patients, 54.23% (2, 524) had pulmonary TB (PTB), 17.76% (827) had EPTB, and 28.00% (1, 303) had concurrent extrapulmonary and pulmonary TB (combined TB). Compared with PTB, EPTB and combined TB were associated with lower hospitalization frequency (2.43 and 2.21 vs. 3.16 times), longer length of stay (10.61 and 11.27 vs. 8.56 days), and higher rate of discharge against medical advice (8.46% and 9.44% vs. 5.67%). EPTB was associated with higher mortality (0.97% vs. 0.24% and 0.31%), higher rate of low birth weight (17.69% vs. 6.79% and 6.22%), worse diagnosis at the first visit (21.16% vs. 34.67% and 44.47%), and worse hospitalization plan situation (4.35% vs. 7.81% and 7.44%), compared with PTB and combined TB. EPTB and combined TB had higher financial burdens (17.67% and 16.94% vs. 13.30%) and higher rates of catastrophic expenditure (8.22% and 9.59% vs. 5.03%), compared with PTB. Meningitis TB (34.18%) was the most frequent form of total extrapulmonary infection and had the highest cost burden and rate of catastrophic expenditure. In conclusion, improved screening approaches for pediatric EPTB are needed to reduce diagnostic challenges and financial burden.